Chronic Sound-induced Tinnitus and Auditory Attention in Animals. (21st May 2019) - Brozoski, Thomas; Wisner, Kurt; Randall, Marc; Caspary, Donald
Highlights: The interaction between auditory attention and chronic tinnitus was examined using a conditioned suppression animal model. Tinnitus was induced in Long–Evans rats by a single unilateral exposure to 120 dB (SPL, peak level) band-limited noise. Months after exposure, animals with tinnitus, without tinnitus, and unexposed controls were tested on two attention tasks. Tinnitus animals had elevated vigilant attention to sound resembling their tinnitus, but not other sounds. Tinnitus animals had inferior selective attention to brief sound events of various compositions. Abstract: Attention may be an important factor in tinnitus. Individuals most disturbed by their tinnitus differ from those who are not in terms of attention allocation. This study used an operant-conditioning animal model to examine the interaction between tinnitus and auditory vigilant attention as well as auditory selective attention. Tinnitus was induced in 90-day-old rats by a unilateral exposure to band-limited noise (120 dB, SPL). Tinnitus testing began 90 days following exposure; afterward animals were divided into three groups: Unexposed controls without tinnitus, Exposed without tinnitus, and Exposed with tinnitus. Tinnitus was evident in the vicinity of 20 kHz. Vigilant attention was quantified by the behavioral (operant) response to unpredictable sound transitions signaling changes in food availability. Tinnitus animals were more vigilant, i.e., responded more rapidly, to 20-kHz tone onsets than Unexposed or Exposed animals without tinnitus. There were no significant vigilant attention differences between groups to non-tinnitus like sounds. The same animals were further trained and tested on a selective attention task. A brief free-field sound cue, consisting of either a short train of identical noise pulses (standard stimulus), or a noise train with one substituted tone pulse (oddball stimulus), cued a left or right nose poke for food. On this selective attention task, Tinnitus animals performed consistently worse than Non-tinnitus or Unexposed control animals regardless of stimulus features. As predicted, animals with behavioral evidence of tinnitus showed tinnitus-related attentional changes, including impaired selective attention but increased vigilance to sounds approximating their tinnitus.